El burnout en futbolistas profesionales en la ciudad de Riobamba - Chimbolema Quinatoa, Jhonnatan Fabricio (2023)
The theme of this research is the analysis of Burnout in professional soccer players in the city of Riobamba who belong to the national soccer teams "Star Club", "Club La Onda" and "Centro Deportivo Olmedo", for which the test was applied. Maslach Burnout Inventory consisting of 15 questions in the form of statements about the professional's feelings and attitudes. Evaluates the feeling of not being able to give more of oneself, both physically and mentally (exhaustion), the presence of a negative attitude of devaluation and loss of interest in work (cynicism) and the existence of doubts about one's own ability to perform work (professional efficacy), to then identify, describe and propose activities that can deal with this syndrome. To approach the investigation, the test was applied to the sample of 50 professional soccer players belonging to the soccer clubs selected for the study. After the application of the test, the respective data analyzes were carried out, from which the mean X̅ of each of the questions posed in the test was extracted, then all the questions for each dimension (Exhaustion, Cynicism and Efficacy) were averaged. Professional). Thus, the averages for each of the dimensions did not exceed the normal limits, thus reaching the conclusion that burnout syndrome does not occur in these soccer teams. Although there are no clear signs of the presence of Burnout in soccer players, a set of activities was proposed that help minimize this type of condition to a certain extent and can even help prevent it from occurring.